2019
DOI: 10.3991/ijet.v14i07.10175
|View full text |Cite
|
Sign up to set email alerts
|

Score Equivalence, Gender Difference, and Testing Mode Preference in a Comparative Study between Computer- Based Testing and Paper-Based Testing

Abstract: Abstract—Score equivalency of two Computer-Based Testing (henceforth CBT) and Paper-and-Pencil-Based Testing (henceforth PBT) versions has turned into a controversial issue during the last decade in Iran. The comparability of mean scores obtained from two CBT and PBT formats of test should be investigated to see if test takers’ testing performance is influenced by the effects of testing administration mode. This research was conducted to examine score equivalency across modes as well as the relationship of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
(21 reference statements)
2
6
0
Order By: Relevance
“…it was easier to implement, could be assess learning outcomes with a large number of students, received feedback instantly, could know directly the exam score) [39], [28] compared to paper and pencil to assess students' learning outcomes in sport or assess sports training programs during the COVID-19 era. The results of this research were also supported by previous studies which reported that most participants showed preference of computer-based that a higher than paper and pencil and also more excellent of computer-based to compare of paper pencil-based [40]. The results of research conducted by Jeong [41], support the results of this study, the data reports that there is a significant difference between computer-based and paper pencil-based performance to assess Korean learning outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…it was easier to implement, could be assess learning outcomes with a large number of students, received feedback instantly, could know directly the exam score) [39], [28] compared to paper and pencil to assess students' learning outcomes in sport or assess sports training programs during the COVID-19 era. The results of this research were also supported by previous studies which reported that most participants showed preference of computer-based that a higher than paper and pencil and also more excellent of computer-based to compare of paper pencil-based [40]. The results of research conducted by Jeong [41], support the results of this study, the data reports that there is a significant difference between computer-based and paper pencil-based performance to assess Korean learning outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…In some studies, test takers outperformed on PPBT rather than CFLT (Carpenter & Alloway, 2018;Hosseini et al, 2014), or no testing administration mode effect was found (Jeong, 2012;Karay et al, 2015;Meyer et al, 2016;Prisacari & Danielson, 2017). Although these results cannot be described as decisive, there is a growing tendency to suggest that two CFLT and PPBT versions are expected to be equivalent across two presentation modes (Alakyleh, 2018;Ebrahimi et al, 2019;Khoshsima et al, 2019;Wang & Shin, 2010). Converting PPBT into CFLT and studying mode effect on testing performance should be done through carefully well-organized empirical investigations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…During the global COVID-19 enforced lockdowns and homeschooling (Pokhrel & Chhetri, 2021) when about half of the world's population (Sandford, 2020) and more than 98% of learners (United Nations, 2020) were affected by the coronavirus outbreak, in-person learning was shifted to remote education (Pokhrel & Chhetri, 2021) and digital learning (Dhawan, 2020) through computer and mobile modes of presentation (Hashemi Toroujeni, et al, In Press). Consequently, due to the synchronizing remarkably arising prevalence and availability of ICT (Gnambs, 2021) and technological advancements (Siddiq & Scherer, 2019) with the ubiquity of computers and smartphones use (Mullis et al, 2017) in daily lives of learners (Daghan, 2017) in last years (Ebrahimi et al, 2019;Khoshsima et al, 2019;Garcia-Laborda and Alcalde-Penalver, 2018) and in the current homeschooling days at increasing spread of COVID-19 (WHO, 2020;Doyle, 2020), many learners have to swapped reading textbooks on screen and from digital resources (Barzillai & Thomson, 2018;Halamish & Elbaz, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It allows to identify certain behaviour patterns, compare them with those which are observed when subjects perform PPT and understand whether it is correct to compare paper-and-pencil and computer-based test forms as equivalent. Not only the technical aspects of the task performance can be the observation object, but also subjects' affective reactions to computer testing (e.g., computer anxiety) (Smith & Caputi, 2007), testing motivation (Chua, 2012) or testing mode preference (Ebrahimi, Toroujeni, & Shahbazi, 2019). That means that equivalence study of «paper» and «computer» test forms should be conducted in the presence of a psychologist or an observer, and not at a distance.…”
mentioning
confidence: 99%